From andragogy to social pedagogy: moral imperative of adult a educational practice (2015)
Teaching method in adult education has gone beyond the divide of pedagogy and andragogy with the proposition of constructivist epistemology for all categories of learners. Learning ought to meet the needs of individual learners and teaching should be learners-centred to ensure social efficiency. Social pedagogy and justifies its implication for the practice of adult education as against andragogy which was hitherto described as the art of teaching adults. Social pedagogy is explained in the contexts of emerging reality that have to guide principles of adult education beyond the 21st century. The author concluded that, social pedagogy is relevant to the practice of adult education in fostering creativity and innovation in learners. The moral imperative that social pedagogy imposes on the practice of adult education, especially in Nigeria is also shown.